Experimental studies on solidification and subcooling characteristics of water-based phase change material (PCM) in a spherical encapsulation for cool thermal energy storage applications. (April 2019) - Vikram, M. Ponrajan; Kumaresan, V.; Christopher, S.; Velraj, R.
Highlights: Subcooling of DI water reduced from −5.4  °C to −2.8  °C with dispersion of sodium chloride and D-sorbitol. Reduction of subcooling would be beneficial to operate the chiller at higher evaporator temperature. 53.5%, 40.5%, and 6% of encapsulated PCM volume solidified during 33.4%, 43.4%, and 23.2% of total solidification duration. Energy saving can be achieved by not operating the chiller during decelerated charging period in CTES system. Addition of dispersants in DI water increased the cooling rate in the subcooling region. Abstract: This work aims to investigate the solidification behavior of de-ionized (DI) water as the base phase change material (PCM) dispersed with various mass fractions of sodium chloride and D-sorbitol in a spherical encapsulation. The DSC analysis of water illustrated that subcooling of DI water increases with respect to cooling rate due to inadequate time to complete the crystallization. The solidification experiments were carried out at a bath temperature of −7  °C and DI water undergoes a subcooling of −5.4  °C. However, the subcooling substantially reduced to −2.8  °C for DI water with 0.5 wt. % sodium chloride and 1 wt. % of D-sorbitol. Accelerated mode of charging prevails in all the PCM samples and the innermost 6% of volume got solidified in decelerated mode. The cooling rate is found to decrease with respect to increase in concentration of the dispersants in subcooling region, but at a particular concentration both dispersants provide the enhanced cooling rate for a given driving potential than DI water. It is concluded that reduction of subcooling and partial charging of water based PCMs would be helpful to enhance the energy efficiency of the cool thermal energy storage (CTES) system.